Continental Perceptions of Englishness, "˜Foreignness" and the Global Turn - Book Review - Boyadzhieva, Ellie (English Studies at NBU, 2017)
Book Details: Title: Continental perceptions of Englishness, "foreignness" and the global turn Author: Audriana Neagu Publisher: Cambridge Scholars Publishing, 120 pages ISBN-13: 978-1-4438-9599-6 ISBN-10: 1-4438-9599-7 Published and distributed online http://www.cambridgescholars.com/continental-perceptions-of-englishness-foreignness-and-the-global-turn